Ginkgolide B Maintains Calcium Homeostasis in Hypoxic Hippocampal Neurons by Inhibiting Calcium Influx and Intracellular Calcium Release - Wang, Li; Lei, Quan; Zhao, Shuai; Xu, WenJuan; Dong, Wei; Ran, JiHua; Shi, QingHai; Fu, JianFeng (Frontiers in Cellular Neuroscience, 2021)
Ginkgolide B (GB), a terpene lactone and active ingredient of Ginkgo biloba, shows protective effects in neuronal cells subjected to hypoxia. We investigated whether GB might protect neurons from hypoxic injury through regulation of neuronal Ca2+ homeostasis. Primary hippocampal neurons subjected to chemical hypoxia (0.7 mM CoCl2) in vitro exhibited an increase in cytoplasmic Ca2+ (measured from the fluorescence of fluo-4), but this effect was significantly diminished by pretreatment with 0.4 mM GB. Electrophysiological recordings from the brain slices of rats exposed to hypoxia in vivo revealed increases in spontaneous discharge frequency, action potential frequency and calcium current magnitude, and all these effects of hypoxia were suppressed by pretreatment with 12 mg/kg GB. Western blot analysis demonstrated that hypoxia was associated with enhanced mRNA and protein expressions of Cav1.2 (a voltage-gated Ca2+ channel), STIM1 (a regulator of store-operated Ca2+ entry) and ryanodine receptor type 1 (which mediates sarcoplasmic reticulum Ca2+ release), and these actions of hypoxia were suppressed by GB. Taken together, our in vitro and in vivo data suggest that GB might protect neurons from hypoxia, in part, by regulating Ca2+ influx and intracellular Ca2+ release to maintain Ca2+ homeostasis.